Characterization of gynoecious cucumber hybrids in relation to morphological descriptors and organoleptic quality - Kumari, Amrita; Kumar, Randhir; Tripathi, Vishal; Bhardwaj, Ajay (Journal of Postharvest Technology, 2021)
The research was performed to study qualitative traits including sensory quality of slicing cucumber parents, their hybrids and standard check. The  present study was carried out with 27 genotypes of cucumber at vegetable research farm and FS&PHT lab of BAC Sabour, Bhagalpur, Bihar. Significant  variations among the genotypes were observed for characters viz., fruit shape, fruit spine color, skin hardness, leaf pubescence density, fruit skin texture  and fruit skin color at tender harvestable maturity. However, limited source of variation were identified for stem pubescence, placental cavity, fruit skin  mottling and flesh color. To determine the best results of quality, fruits were subjected for sensory analysis of bitterness using a 9-point hedonic scale.  Study of qualitative traits and sensory analysis in gynoecious cucumber hybrids suggest that it is a promising method to maintain quality parameters of  cucumber for economic returns.
Keywords: Bitterness; downy mildew; gynoecious hybrids; hedonic scale; sensory quality